Action Sentence Compatibility Effect With Swallow-Related Action Words. - Kurosu, Atsuko; Pratt, Sheila R.; Palmer, Catherine; Shaiman, Susan (Perspectives of the ASHA Special Interest Groups, 2026)
Purpose: The action sentence compatibility effect (ACE) is consistent with embodiment theory in that facilitation and interference are observed when the directionality implied by action sentences and that of physical responses are congruent and incongruent, respectively. However, the impact of action word categories within sentences has not been assessed systematically within the ACE framework. In this study, words describing ingestive and aerodigestive functions (e.g., swallow or vomit) were of particular interest because they convey directionality, and therefore, the ACE should apply to their processing within sentences. They also are associated with both voluntary and involuntary motor control, which might influence the ACE. The purpose of this study was to assess the impact of directional action sentences (with and without swallow-related words) using a sensibility judgment task that required a manual response. This investigation has clinical relevance because, during videofluoroscopic swallow examination, patients commonly are commanded to swallow (command swallow). If there is a directional relationship between swallow-related words and motor performances, the command swallow may influence video-fluoroscopic results. Method: Two experiments were conducted with healthy adults using the classic ACE paradigm and sentences from Borreggine and Kaschak (2006). Sentences with ingestive and aerodigestive functions (swallow-related) also were included. Results: Both experiments failed to demonstrate the ACE. An interaction was not found between movement and directionality for sentences containing swallow-related action words. Conclusions: The results suggested a lack of or limited directionality in swallow-related words, potentially limiting their influence on videofluoroscopic testing. However, this conclusion should be validated within other embodied frameworks.